Culture bound syndromes in a group of Xhosa with psychiatric disorders - E. N. Shezi; L. R. Uys (AOSIS, 1997)
The article describes the culture bound syndromes found amongst a sample of 40 psychiatric patients seen at Umzimkulu Hospital serving mainly Xhosa speaking people. A CBS could be identified in 15 of these patients. CBS similar to four of the six syndromes found in these patients were Ascribed in DSM IV, while two were not The CBS were compared to the Axis 1 diagnoses, and the different syndromes described.